Randomized Controlled Trial of Gastrocnemius Muscle Analysis Using Surface Electromyography and Ultrasound in Different Striking Patterns of Young Women’s Barefoot Running - Yuwei Liu; Justin Fernandez (Physical Activity and Health)
Running has become a popular national sport, increasing the risk of related injuries. Different striking patterns, such as forefoot (FFS) and rearfoot striking (RFS), contribute to varying injury types and influence muscle dynamics in the lower leg. This study examines the differences in force modes and muscle morphology of the gastrocnemius calf muscle under distinct striking patterns. A randomized controlled trial was conducted with twenty young female runners, ten typically striking on their forefoot and ten on their rearfoot, all without lower limb injuries in the past six months. Pre-run ultrasound measurements assessed the muscle thickness and pennation angle of the right gastrocnemius muscle, and electromyography (EMG) data were recorded post-treadmill run. An independent sample t-test compared the two groups. At the loading response stage, there was no significant difference in the root mean square (RMS) amplitude of the gastrocnemius muscle between the FFS and RFS groups, likely due to the delay between muscle activation and force generation. However, from mid-swing to late swing, the FFS group exhibited higher RMS amplitude, reflecting significantly greater muscle activation in the gastrocnemius muscle. This suggests increased muscle stiffness in the FFS group to cope with ground reaction forces, alongside higher activation and median frequency values in both the gastrocnemius medialis (GM) and gastrocnemius lateralis (GL), making the FFS group more prone to fatigue. Additionally, the gastrocnemius muscle thickness and fiber length in the RFS group were greater than in the FFS group. One limitation of this study is that inferring greater muscle explosive force solely based on muscle thickness and fiber length may be insufficient. Future research should incorporate biomechanical indicators, such as force plate testing, to better understand the relationship between muscle structure and function across different running styles.